Inorganic water-based carbon nanotube anti-metal corrosion coating and preparation method thereof

By adding modified carbon nanotubes and modified water-based epoxy resin to anti-metal corrosion coatings, a dense network structure is formed, which solves the problems of poor environmental protection and short corrosion resistance of existing coatings, and achieves high adhesion and resistance. Corrosive and degradable coating properties.

CN119463599APending Publication Date: 2025-02-18CHINA TOWER CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411672806.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing anti-metal corrosion coatings have problems such as poor environmental protection, short corrosion resistance, high surface treatment requirements, poor dispersion stability of color filler, and flash corrosion easily after coating.

Method used

Using an inorganic aqueous carbon nanotube anti-metal corrosion coating incorporated with carbon nanotubes, a dispersant is added to make the carbon nanotubes evenly disperse in the coating to form a dense Network structure to improve corrosion resistance of the coating.

Benefits of technology

It realizes the excellent water-based substrate, non-toxic and harmless formula, and degradable properties of the coating, significantly reduces the emission of volatile organic compounds, improves the adhesion, corrosion resistance and durability of the coating, and extends the use. life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005146301550000091
    Figure BDA0005146301550000091
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to an inorganic water-based carbon nanotube metal corrosion prevention coating and a preparation method thereof. The inorganic water-based carbon nanotube metal corrosion prevention coating comprises the following components in parts by weight: 15-20 parts of modified carbon nanotubes, 5-10 parts of modified water-based epoxy resin, 20-25 parts of a hydroxyl acrylic emulsion, 20-25 parts of a filler, 1-3 parts of a silane coupling agent, 1-4 parts of a flatting agent, 2-5 parts of a dispersing agent, 1-4 parts of a flash rust inhibitor, 1-3 parts of a coalescing agent, 2-4 parts of a defoaming agent and 30-50 parts of deionized water, the preparation method comprises the following steps: stirring the modified carbon nanotubes, the modified water-borne epoxy resin, the hydroxyl acrylic emulsion, the filler, the silane coupling agent, the flatting agent, the dispersing agent, the flash-rust inhibitor, the coalescing agent, the defoaming agent and the deionized water in parts by weight at 40-50 DEG C for 20-30 minutes. The coating prepared by the method disclosed by the invention is uniform in dispersion, good in adhesive force, excellent in corrosion resistance and durability stability, and long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and more specifically to an inorganic water-based carbon nanotube anti-metal corrosion coating and a preparation method thereof. Background Art

[0002] In recent years, the fundamental reason why anti-corrosion coatings have become a hot topic in the industry is the rapid growth of market demand. Cases of damage caused by metal corrosion are widespread in various fields, causing huge losses to the national economy. According to statistics, the economic losses caused by corrosion in the world are about 700 billion US dollars each year, accounting for 2% to 4% of the gross national product of various countries. With the rapid development of my country's economic construction, there has been an extraordinary growth in many fields such as construction, transportation, petrochemicals, hydropower, etc., which has led to a rapid growth in demand for related supporting products, and the anti-corrosion coating industry is like a duck in water.

[0003] Traditional metal anticorrosion coatings mainly include epoxy resin anticorrosion coatings, polyurethane anticorrosion coatings and zinc-rich anticorrosion coatings, most of which are oily coatings. During use, there are a large number of organic volatiles, which are harmful to the human body and cause environmental pollution. In addition, environmentally harmful anti-rust pigments are added to zinc-rich anticorrosion coatings. The strength, impact resistance and conductivity of epoxy resin after curing are poor and cannot meet the requirements of the process. Polyurethane has poor impact resistance, easy bubbles when exposed to moisture, and high insulation of general polyurethane, which is easy to generate static electricity, which limits its application in certain fields. Compared with oily coatings, inorganic water-based coatings are more environmentally friendly and have been developed in recent years. They have the advantage of good environmental protection. Inorganic water-based zinc-rich coatings are a commonly used metal anticorrosion coating on the market. They are mainly composed of high molar ratio silicate resins, additives and zinc powder. The base materials include sodium silicate, potassium silicate, lithium silicate aqueous solution, etc., among which lithium silicate is a commonly used base material. It is widely used for long-term corrosion protection of steel structures exposed to marine atmosphere, high temperature and various environments, such as offshore platforms, dock steel columns, ships, containers, various dock equipment, offshore platforms, steel components of large buildings, etc. However, there are many defects in practical applications. Its porosity affects its anti-corrosion performance in certain specific environments. In addition, it has high requirements for substrate treatment, the paint film is relatively brittle, and it is easily affected by construction and curing conditions, as well as limited selection of supporting coatings.

[0004] Carbon nanotubes are a kind of one-dimensional quantum hollow tube structure material with a special structure. They have attracted extensive attention in the research and development of new coatings due to their excellent chemical stability, thermal stability and mechanical stability. In previous reports, using carbon nanotubes as fillers in water-based inorganic zinc-rich coatings and water-based acrylic coatings can also significantly improve their corrosion resistance. However, due to the unique structure and surface properties of this material, it is easy to aggregate and form agglomerates when directly added to the coating, and even produce more micropores, which seriously affects the corrosion resistance.

[0005] Most of the commonly used anti-metal corrosion coatings are oily coatings. Although they have good anti-corrosion performance, they contain a large amount of organic volatiles during use, which are harmful to the human body and cause environmental pollution. Another type of inorganic water-based coating is a type of coating developed in recent years. It has the advantage of good environmental protection, but generally has the problems of short anti-corrosion period, high requirements for surface treatment, poor dispersion stability of pigments and fillers, and easy flash corrosion after coating. Therefore, the present invention analyzes various aspects of the coating to solve the above problems and provides a new type of environmentally friendly anti-metal corrosion coating with excellent comprehensive performance. Summary of the invention

[0006] The purpose of the present invention is to provide an inorganic water-based metal anti-corrosion coating doped with carbon nanotubes and a preparation method thereof, so as to improve the comprehensive performance of the metal anti-corrosion coating. The preparation method is simple and easy to implement, convenient for construction, and has a low content of volatile organic matter. The volatile organic matter VOCs is 30.2 mg / m 3 , safe and environmentally friendly; the prepared anti-metal corrosion coating has good adhesion, with an adhesion grade of 0, excellent corrosion resistance and durable stability, and the anti-corrosion life of the coating on metal is 1 to 2 years, with salt spray resistance of 480 hours and aqueous solution resistance of 400 hours. Dispersant is added to the coating to make the carbon nanotubes evenly dispersed in the coating, so that the coating formed by the entire coating has good uniformity of performance and long service life.

[0007] The coating of the present invention uses multi-walled carbon nanotubes (MWCNTs), which are composed of multiple concentric carbon nanotube layers, such as a series of microtubes nested in each other. They usually have a larger diameter, ranging from 2 to 100 nanometers or larger, depending on the number of walls. The composition of multi-walled carbon nanotubes is almost entirely carbon, with a purity of more than 95%. This pure carbon composition and its unique layered structure give these nanotubes excellent mechanical, thermal and electrical properties. Multi-walled carbon nanotubes are generally suitable for applications where mechanical strength is critical. Adding them to the coating can enhance the hardness of the coating, as well as corrosion resistance.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] The first aspect of the present invention provides an inorganic water-based carbon nanotube anti-metal corrosion coating, which comprises, by weight, 15 to 20 parts of modified carbon nanotubes, 5 to 10 parts of modified water-based epoxy resin, 20 to 25 parts of hydroxyl acrylic emulsion, 20 to 25 parts of filler, 1 to 3 parts of silane coupling agent, 1 to 4 parts of leveling agent, 2 to 5 parts of dispersant, 1 to 4 parts of anti-flash rust agent, 1 to 3 parts of film-forming aid, 2 to 4 parts of defoaming agent and 30 to 50 parts of deionized water;

[0010] The modified carbon nanotubes are obtained by modifying multi-walled carbon nanotubes with an acidic solution and then with acrylic acid; and the modified waterborne epoxy resin is obtained by modifying waterborne epoxy resin with an inhibitor.

[0011] According to a preferred embodiment, a method for preparing modified carbon nanotubes comprises the following steps:

[0012] 0.5 g of multi-walled carbon nanotubes were ultrasonically stirred in 200-250 mL of acidic solution for 1 h, diluted with distilled water and separated by vacuum filtration, washed with deionized water until neutral, and then vacuum dried at 60° C. for 12 h, and ground to obtain pretreated multi-walled carbon nanotubes;

[0013] 0.05 g of pretreated multi-walled carbon nanotubes were dispersed in 40-50 mL of toluene solution and ultrasonically treated for 1 h. Acrylic acid and azobisisobutyronitrile initiators were added dropwise in sequence with stirring in a water bath at 60 ° C. After stirring for 6 h, the mixture was vacuum filtered and separated. The acrylic acid monomer, initiator and solvent were removed with deionized water, and then vacuum dried at 60 ° C for 12 h. The modified carbon nanotubes were obtained after grinding.

[0014] More preferably, the acidic solution is H 2 SO 4 Solution and HNO 3 The solutions are mixed in an optimal ratio of 3:1 to obtain a mixed solution, wherein the pH of the acidic solution is 3-5.

[0015] More preferably, the initiator is azobisisobutyronitrile, and the mass ratio of acrylic acid to azobisisobutyronitrile is (100-120):(1-5).

[0016] Under the preferred scheme, a more preferred method for preparing a modified water-based epoxy resin comprises the following steps: adding a water-based epoxy resin and an inhibitor to tetrahydrofuran, stirring the reaction at 70°C to 80°C for 4 to 6 hours, and then removing the solvent by rotary evaporation, adding water to extract the product, and then separating the liquids and rotary evaporating to remove water to obtain a modified water-based epoxy resin.

[0017] More preferably, the polymerization inhibitor is one or more of 2,6-di-tert-butyl-p-methylphenol, 4,4'-dihydroxybiphenyl, and bisphenol A.

[0018] More preferably, the mass ratio of the waterborne epoxy resin, the polymerization inhibitor and tetrahydrofuran is (3-5):0.1:(15-20).

[0019] In a preferred embodiment, the silane coupling agent is one or more of vinyl silane, aminosilane, epoxysilane, and mercaptosilane; the leveling agent is one or more of polypropylene resin, cellulose acetate leveling agent, and pure polyacrylate leveling agent; the dispersant is one or more of polyacrylic acid derivatives, polyether derivatives, and sodium hexametaphosphate; the anti-flash rust agent is one or more of polyphosphate and ARCH100S anti-flash rust agent; the film-forming aid is one or more of propylene glycol, methanol, and propylene glycol butyl ether; the defoaming agent is one or more of tributyl phosphate and defoaming agent D160.

[0020] In a preferred embodiment, the filler is one or more of titanium dioxide, talcum powder, and mica powder.

[0021] The second aspect of the present invention provides a method for preparing any of the above inorganic water-based carbon nanotube anti-metal corrosion coatings, comprising the following steps: stirring modified carbon nanotubes, modified water-based epoxy resin, hydroxyl acrylic emulsion, filler, silane coupling agent, leveling agent, dispersant, anti-flash rust agent, film-forming aid, defoaming agent and deionized water at 40°C to 50°C for 20 to 30 minutes according to the weight parts as described in claim 1.

[0022] Beneficial effects of the present invention

[0023] 1. The water-based anti-metal corrosion coating of the present invention has significant advantages in the field of environmental protection due to its excellent water-based base material, non-toxic and harmless formula and degradable characteristics. It not only greatly reduces the emission of volatile organic compounds during production and use, but also effectively reduces environmental pollution and resource consumption.

[0024] 2. The water-based anti-metal corrosion coating of the present invention is based on the research of traditional anti-metal corrosion coatings, and carbon nanotubes are added to the formula. Since the carbon nanotube material has a special tubular morphology, when it is dispersed in the coating material, it is very easy to form an internally interwoven dense network structure, so the coating can largely prevent the corrosive medium from passing through the coating and corroding the base metal material. On the other hand, since the standard potential of the carbon nanotube material is more positive than the potential of the metal material, after the carbon nanotube material is added to the metal coating, under the action of the potential difference, the coating metal will undergo anodic polarization and then be passivated. Therefore, from the perspective of electrochemistry, the carbon nanotube material uniformly dispersed in the coating can effectively slow down the corrosion rate of the coating to play a role in protecting the base metal material. Feng Lajun et al. took the carbon nanotube fluorocarbon composite coating as the research object, and studied the corrosion resistance of the coating by analyzing the changes in its electrochemical impedance spectrum. The results showed that multi-walled carbon nanotubes significantly improved the corrosion resistance of the material by forming chemically stable C-F bonds. Based on the above conclusions, the present invention utilizes the excellent anti-corrosion mechanism of carbon nanotubes to enable it to exhibit more outstanding technical advantages than traditional anti-metal corrosion coatings in actual applications.

[0025] 3. The modified epoxy resin used in the present invention makes the water-based anti-metal corrosion coating have excellent adhesion, chemical corrosion resistance, wear resistance, and dimensional stability, and has good processing performance and curing flexibility. In addition, the coating surface formed after curing is smooth and has high hardness, which can significantly improve the overall performance and service life of the coating.

[0026] 4. The inorganic water-based carbon nanotube anti-metal corrosion coating of the present invention has the advantage of rust-resistant coating in practical applications. It can be directly coated without completely removing the rust on the metal surface. It not only simplifies the construction steps and improves work efficiency, but also effectively isolates the direct contact between the metal and the corrosive environment, further extending the service life of the metal.

[0027] 5. The existing anti-metal corrosion coating has a significant problem that when applied in an environment of high humidity, rainy days or high temperature, the solvent in the coating evaporates too quickly or water vapor accumulates on the surface of the base layer, which may cause bubbles to form. The inorganic water-based carbon nanotube anti-metal corrosion coating in the present invention directly uses water as a solvent, so the volatilization rate after coating is greatly reduced, effectively solving the problem of bubbles caused by too fast solvent volatilization, and has great technical advantages compared to existing coatings. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0029] Source of materials:

[0030] 1. The hydroxy acrylic emulsion used in the present invention is homemade. For the preparation method, see reference: Wang Yuebin, Shanghai Coatings, 2024, 62(01): 14-18.

[0031] 2. The multi-walled carbon nanotube material (also called original multi-walled carbon nanotube) used in the present invention is homemade. For the preparation method, please refer to the reference: Shang Yingshuang. "Preparation of multi-walled carbon nanotube / graphite / polyetheretherketone composite materials and study on their friction properties". Jilin University, 2018.

[0032] 3. The waterborne epoxy resin used in the present invention is homemade. For the preparation method, please refer to the reference: Cheng Meng, Bao Guangzhi, Guo Hongjun, et al. "Study on the influence of different waterborne epoxy resins on the performance of SBR modified emulsified asphalt". Highway, 2024, 69(09): 42-47.

[0033] 4. Unless otherwise specified, the raw materials used in the present invention can be obtained through commercial channels.

[0034] The invention discloses an inorganic water-based carbon nanotube anti-metal corrosion coating, which comprises the following components in parts by weight: 15-20 parts of modified carbon nanotubes, 5-10 parts of modified water-based epoxy resin, 20-25 parts of hydroxy acrylic emulsion, 20-25 parts of filler, 1-3 parts of silane coupling agent, 1-4 parts of leveling agent, 2-5 parts of dispersant, 1-4 parts of anti-flash rust agent, 1-3 parts of film-forming aid, 2-4 parts of defoaming agent and 30-50 parts of deionized water.

[0035] The modified carbon nanotubes are obtained by modifying multi-walled carbon nanotubes with an acid solution (pH value is 3-5) and then with acrylic acid; and the modified waterborne epoxy resin is obtained by modifying waterborne epoxy resin with an inhibitor.

[0036] Specifically, the filler is one or more of titanium dioxide, talc, and mica powder; the silane coupling agent is one or more of vinyl silane, aminosilane, epoxysilane, and mercaptosilane; the leveling agent is one or more of polypropylene resin, cellulose acetate leveling agent, and pure polyacrylate leveling agent; the dispersant is one or more of polyacrylic acid derivatives, polyether derivatives, and sodium hexametaphosphate; the anti-flash rust agent is one or more of polyphosphate and ARCH100S anti-flash rust agent; the film-forming aid is one or more of propylene glycol, methanol, and propylene glycol butyl ether; the defoaming agent is one or more of tributyl phosphate and defoaming agent D160.

[0037] A preferred method for preparing modified carbon nanotubes comprises the following steps:

[0038] Pretreatment: 0.5 g of original multi-walled carbon nanotubes were ultrasonically stirred (150 W, 100 KHz) in 200 mL of acidic solution for 1 h, diluted with distilled water and separated by vacuum filtration, then washed with deionized water until neutral, and then the nanotubes were vacuum dried at 60 ° C for 12 h, and ground to obtain pretreated multi-walled carbon nanotubes;

[0039] Acrylic acid modification: Take 0.05g of pretreated multi-walled carbon nanotubes and disperse them in 40mL of toluene solution for ultrasonic treatment for 1h. Then, add acrylic acid and azobisisobutyronitrile initiator in sequence with stirring in a water bath at 60℃. After stirring for 6h, vacuum filtration and separation are carried out. Then, the acrylic acid monomer, initiator and solvent are removed with deionized water, and then vacuum dried at 60℃ for 12h. After grinding, modified carbon nanotubes are obtained.

[0040] More preferably, the acidic solution is H 2 SO 4 Solution and HNO 3 The solutions (both solutions have a concentration of 98%) are mixed in an optimal ratio of 3:1 to obtain a mixed solution; the initiator is azobisisobutyronitrile, and the mass ratio of acrylic acid to the azobisisobutyronitrile initiator is (100-120):(1-5).

[0041] A preferred method for preparing a modified waterborne epoxy resin comprises the following steps: adding a waterborne epoxy resin and a polymerization inhibitor into tetrahydrofuran, stirring and reacting at 70°C to 80°C for 4 to 6 hours, then removing the solvent by rotary evaporation, adding water to extract the product, separating the liquids and rotary evaporating to remove water to obtain a modified waterborne epoxy resin.

[0042] More preferably, the mass ratio of waterborne epoxy resin, polymerization inhibitor and tetrahydrofuran is (3-5):0.1:(15-20); the polymerization inhibitor is one or more of 2,6-di-tert-butyl-p-methylphenol, 4,4'-dihydrobiphenyl and bisphenol A.

[0043] A method for preparing the above-mentioned inorganic water-based carbon nanotube anti-metal corrosion coating comprises the following steps: adding modified carbon nanotubes, modified water-based epoxy resin, hydroxy acrylic emulsion, filler, silane coupling agent, leveling agent, dispersant, anti-flash rust agent, film-forming aid, defoaming agent and deionized water into an emulsifying pot according to the above-mentioned parts by weight, stirring at a temperature of 40°C to 50°C for 20 to 30 minutes to obtain the product.

[0044] Due to the application of the above technical solution, the patent of the present invention has the following characteristics compared with the prior art: the anti-metal corrosion coating prepared by the present invention has good adhesion, excellent corrosion resistance and durable stability, and a dispersant is added to the coating to make the carbon nanotubes dispersed evenly in the coating, so that the coating formed by the entire coating has good uniformity of performance and a long service life.

[0045] Example 1

[0046] The inorganic water-based carbon nanotube anti-metal corrosion coating comprises, by weight, 15 parts of modified carbon nanotubes, 5 parts of modified water-based epoxy resin, 10 parts of hydroxy acrylic emulsion, 20 parts of filler, 1 part of vinyl silane, 1 part of polypropylene resin, 2 parts of polyacrylic acid derivatives, 1 part of polyphosphate, 1 part of propylene glycol, 2 parts of tributyl phosphate and 30 parts of deionized water. The filler is talcum powder with a particle size of 300 meshes.

[0047] The preparation method of modified waterborne epoxy resin comprises the following steps: adding waterborne epoxy resin and polymerization inhibitor into tetrahydrofuran, stirring and reacting at 75°C for 5 hours, then removing the solvent by rotary evaporation, adding water to extract the product, separating the liquids and rotary evaporation to remove water to obtain modified waterborne epoxy resin.

[0048] The preparation method of modified carbon nanotubes comprises the following steps: 0.5 g of original multi-walled carbon nanotubes are dissolved in 200 mL of H 2 SO 4 and HNO 3The mixed solution was ultrasonically stirred (150W, 100KHz) for 1h. It was then diluted with distilled water, separated by a vacuum filtration device, and rinsed with deionized water until pH = 7. The obtained sample was then dried in a vacuum oven at 60°C for 12h, and the dried product was ground with a mortar to obtain pretreated multi-walled carbon nanotubes. The second step of the experiment was to modify the pretreated multi-walled carbon nanotubes with acrylic acid. 0.05g of pretreated multi-walled carbon nanotubes was dispersed in 40mL of toluene solution and treated with ultrasound for 1h, uniformly dispersed to obtain a dispersion. When the water bath temperature was raised to 60°C, the dispersion was transferred to a water bath and stirred, and acrylic acid and azobisisobutyronitrile initiators were slowly added dropwise in sequence. The reaction mixture was continuously stirred for 6h at 60°C, with a stirring speed of 200r / min, and then separated again by a vacuum filtration device, and the product was rinsed with deionized water to remove residual acrylic acid monomer, initiator and solvent. Finally, the obtained functionalized carbon nanotubes were dried in a vacuum oven at 60 °C for 12 h, and the final product was ground for later use.

[0049] The preparation method of an inorganic water-based carbon nanotube anti-metal corrosion coating comprises the following steps: adding modified carbon nanotubes, modified water-based epoxy resin, hydroxy acrylic emulsion, filler, vinyl silane, polypropylene resin, polyacrylic acid derivative, polyphosphate, propylene glycol, tributyl phosphate and deionized water into an emulsifying pot according to the weight parts provided in this embodiment, stirring at 40° C. for 25 minutes at a stirring rate of 200 r / min to obtain a product.

[0050] Example 2

[0051] The inorganic water-based carbon nanotube anti-metal corrosion coating comprises, by weight, 16 parts of modified carbon nanotubes, 7 parts of modified water-based epoxy resin, 11 parts of hydroxy acrylic emulsion, 21 parts of filler, 1.5 parts of aminosilane, 1.5 parts of cellulose acetate leveling agent, 2.5 parts of polyether derivative, 1.5 parts of polyphosphate, 1.5 parts of methanol, 2.5 parts of tributyl phosphate and 35 parts of deionized water. The filler is talcum powder with a particle size of 300 meshes.

[0052] In this embodiment, the preparation method of the modified water-based epoxy resin and the preparation method of the modified carbon nanotubes are exactly the same as the preparation method provided in Example 1; in the preparation method of the inorganic water-based anti-metal corrosion coating, except that the components and the number of portions of the coating adopt the components and the number of portions provided in this embodiment, the remaining steps are prepared according to the preparation method provided in Example 1.

[0053] Example 3

[0054] The inorganic water-based carbon nanotube anti-metal corrosion coating comprises, by weight, 17 parts of modified carbon nanotubes, 8 parts of modified water-based epoxy resin, 12 parts of hydroxy acrylic emulsion, 22 parts of filler, 2 parts of aminosilane, 2 parts of cellulose acetate butyl leveling agent, 3 parts of polyether derivative, 2 parts of polyphosphate, 2 parts of methanol, 3 parts of tributyl phosphate and 40 parts of deionized water. The filler is titanium dioxide with a particle size of 300 meshes.

[0055] In this embodiment, the preparation method of the modified water-based epoxy resin and the preparation method of the modified carbon nanotubes are exactly the same as the preparation method provided in Example 1; in the preparation method of the inorganic water-based anti-metal corrosion coating, except that the components and the number of portions of the coating adopt the components and the number of portions provided in this embodiment, the remaining steps are prepared according to the preparation method provided in Example 1.

[0056] Example 4

[0057] The inorganic water-based carbon nanotube anti-metal corrosion coating comprises, by weight, 18 parts of modified carbon nanotubes, 9 parts of modified water-based epoxy resin, 13 parts of hydroxy acrylic emulsion, 23 parts of filler, 2.5 parts of epoxy silane, 3 parts of pure polyacrylate leveling agent, 4 parts of sodium hexametaphosphate, 3 parts of ARCH100S anti-flash rust agent, 2.5 parts of propylene glycol butyl ether, 3.5 parts of defoamer D160, and 45 parts of deionized water. The filler is titanium dioxide with a particle size of 300 meshes.

[0058] In this embodiment, the preparation method of the modified water-based epoxy resin and the preparation method of the modified carbon nanotubes are exactly the same as the preparation method provided in Example 1; in the preparation method of the inorganic water-based anti-metal corrosion coating, except that the components and the number of portions of the coating adopt the components and the number of portions provided in this embodiment, the remaining steps are prepared according to the preparation method provided in Example 1.

[0059] Example 5

[0060] The inorganic water-based carbon nanotube anti-metal corrosion coating comprises, by weight, 20 parts of modified carbon nanotubes, 10 parts of modified water-based epoxy resin, 15 parts of hydroxy acrylic emulsion, 25 parts of filler, 3 parts of mercaptosilane, 4 parts of pure polyacrylate leveling agent, 5 parts of sodium hexametaphosphate, 4 parts of ARCH100S anti-flash rust agent, 3 parts of propylene glycol butyl ether, 4 parts of defoamer D160, and 50 parts of deionized water. The filler is mica powder with a particle size of 300 meshes.

[0061] In this embodiment, the preparation method of the modified water-based epoxy resin and the preparation method of the modified carbon nanotubes are exactly the same as the preparation method provided in Example 1; in the preparation method of the inorganic water-based anti-metal corrosion coating, except that the components and the number of portions of the coating adopt the components and the number of portions provided in this embodiment, the remaining steps are prepared according to the preparation method provided in Example 1.

[0062] Comparative Example 1

[0063] The inorganic water-based anti-metal corrosion coating comprises, by weight, 15 parts of multi-walled carbon nanotubes, 5 parts of modified water-based epoxy resin, 10 parts of hydroxy acrylic emulsion, 20 parts of filler, 1 part of vinyl silane, 1 part of polypropylene resin, 2 parts of polyacrylic acid derivatives, 1 part of polyphosphate, 1 part of propylene glycol, 2 parts of tributyl phosphate and 30 parts of deionized water. The filler is talcum powder with a particle size of 300 meshes.

[0064] In this comparative example, the preparation method of the modified water-based epoxy resin is exactly the same as the preparation method provided in Example 1; in the preparation method of the inorganic water-based anti-metal corrosion coating, except that multi-walled carbon nanotubes are used instead of modified carbon nanotubes, the coating is prepared according to the preparation method of the inorganic water-based anti-metal corrosion coating provided in Example 1.

[0065] Comparative Example 2

[0066] The inorganic water-based anti-metal corrosion coating comprises, by weight, 15 parts of modified carbon nanotubes, 5 parts of water-based epoxy resin, 10 parts of hydroxy acrylic emulsion, 20 parts of filler, 1 part of vinyl silane, 1 part of polypropylene resin, 2 parts of polyacrylic acid derivatives, 1 part of polyphosphate, 1 part of propylene glycol, 2 parts of tributyl phosphate and 30 parts of deionized water. The filler is talcum powder with a particle size of 300 meshes.

[0067] In this comparative example, the preparation method of the modified water-based epoxy resin is exactly the same as the preparation method provided in Example 1; in the preparation method of the inorganic water-based anti-metal corrosion coating, except that the modified water-based epoxy resin is replaced by the water-based epoxy resin, the coating is prepared according to the preparation method of the inorganic water-based anti-metal corrosion coating provided in Example 1.

[0068] Comparative Example 3

[0069] The inorganic water-based anti-metal corrosion coating comprises, by weight, 15 parts of modified carbon nanotubes, 5 parts of modified water-based epoxy resin, 20 parts of fillers, 1 part of vinyl silane, 1 part of polypropylene resin, 2 parts of polyacrylic acid derivatives, 1 part of polyphosphate, 1 part of propylene glycol, 2 parts of tributyl phosphate and 30 parts of deionized water. The filler is talcum powder with a particle size of 300 meshes.

[0070] In this comparative example, the preparation method of the modified water-based epoxy resin is exactly the same as the preparation method provided in Example 1; in the preparation method of the inorganic water-based anti-metal corrosion coating, except that the modified hydroxyl acrylic emulsion is not added, the coating is prepared according to the preparation method of the inorganic water-based anti-metal corrosion coating provided in Example 1.

[0071] The coatings prepared in the above Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to relevant performance tests, and the test methods and test results are shown in Table 1 below.

[0072] Table 1. Performance test table of inorganic water-based anti-metal corrosion coating of the present invention

[0073]

[0074] It can be seen from Table 1 that, compared with Comparative Examples 1 to 3, the inorganic water-based carbon nanotube anti-metal corrosion coatings prepared in Examples 1 to 5 have higher adhesion, better moisture and heat resistance, salt spray resistance, and greater hardness.

[0075] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An inorganic water-based carbon nanotube anti-metal corrosion coating, characterized in that: The components are as follows: 15-20 parts of modified carbon nanotubes, 5-10 parts of modified waterborne epoxy resin, 20-25 parts of hydroxy acrylic emulsion, 20-25 parts of filler, 1-3 parts of silane coupling agent, 1-4 parts of leveling agent, 2-5 parts of dispersant, 1-4 parts of flash rust preventer, 1-3 parts of film-forming aid, 2-4 parts of defoamer and 30-50 parts of deionized water. The modified carbon nanotubes are obtained by modifying the original multi-walled carbon nanotubes with an acid solution and then with acrylic acid; and the modified waterborne epoxy resin is obtained by modifying the waterborne epoxy resin with an inhibitor.

2. The inorganic water-based carbon nanotube anti-metal corrosion coating according to claim 1, characterized in that: The method for preparing the modified carbon nanotubes comprises the following steps: 0.5 g of original multi-walled carbon nanotubes were ultrasonically stirred in 200-250 mL of acidic solution for 1 h, diluted with distilled water and separated by vacuum filtration, washed with deionized water until neutral, and then vacuum dried at 60 ° C for 12 h, and ground to obtain pretreated multi-walled carbon nanotubes; 0.05 g of pretreated multi-walled carbon nanotubes were dispersed in 40-50 mL of toluene solution and ultrasonically treated for 1 h. Acrylic acid and azobisisobutyronitrile initiators were added dropwise in sequence with stirring in a water bath at 60 ° C. After stirring for 6 h, the mixture was vacuum filtered and separated. The acrylic acid monomer, initiator and solvent were removed with deionized water, and then vacuum dried at 60 ° C for 12 h. The modified carbon nanotubes were obtained after grinding.

3. The inorganic water-based carbon nanotube anti-metal corrosion coating according to claim 1 or 2, characterized in that: The acidic solution is a mixed solution obtained by mixing H2SO4 solution and HNO3 solution in a ratio of 3:1, and the pH of the acidic solution is 3-5.

4. The inorganic water-based carbon nanotube anti-metal corrosion coating according to claim 2, characterized in that: The initiator is azobisisobutyronitrile, and the mass ratio of acrylic acid to azobisisobutyronitrile is (100-120):(1-5); the stirring power of the ultrasonic stirring is 150W, and the stirring frequency is 100KHz.

5. The inorganic water-based carbon nanotube anti-metal corrosion coating according to claim 1, characterized in that: The preparation method of the modified waterborne epoxy resin comprises the following steps: adding the waterborne epoxy resin and the polymerization inhibitor into tetrahydrofuran, stirring the reaction at 70°C to 80°C for 4 to 6 hours, and then removing the solvent by rotary evaporation, adding water to extract the product, and then separating the liquids and rotary evaporating to remove the water to obtain the modified waterborne epoxy resin.

6. The inorganic water-based carbon nanotube anti-metal corrosion coating according to claim 5, characterized in that: The polymerization inhibitor is one or more of 2,6-di-tert-butyl-p-methylphenol, 4,4'-dihydroxybiphenyl and bisphenol A.

7. The inorganic water-based carbon nanotube anti-metal corrosion coating according to claim 5, characterized in that: The mass ratio of the waterborne epoxy resin, the polymerization inhibitor and tetrahydrofuran is (3-5):0.1:(15-20).

8. The inorganic water-based carbon nanotube anti-metal corrosion coating according to claim 1, characterized in that: The silane coupling agent is one or more of vinyl silane, aminosilane, epoxysilane, and mercaptosilane; the leveling agent is one or more of polypropylene resin, cellulose acetate leveling agent, and pure polyacrylate leveling agent; the dispersant is one or more of polyacrylic acid derivatives, polyether derivatives, and sodium hexametaphosphate; the anti-flash rust agent is one or more of polyphosphate and ARCH100S anti-flash rust agent; the film-forming aid is one or more of propylene glycol, methanol, and propylene glycol butyl ether; the defoaming agent is one or more of tributyl phosphate and defoaming agent D160.

9. The inorganic water-based carbon nanotube anti-metal corrosion coating according to claim 1, characterized in that: The filler is one or more of titanium dioxide, talcum powder and mica powder.

10. A method for preparing the inorganic water-based carbon nanotube anti-metal corrosion coating according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: stirring modified carbon nanotubes, modified waterborne epoxy resin, hydroxy acrylic emulsion, filler, silane coupling agent, leveling agent, dispersant, anti-flash rust agent, film-forming aid, defoamer and deionized water at 40°C to 50°C for 20 to 30 minutes according to the weight parts as stated in claim 1.

Citation Information

Cited By

  • Corrosion-resistant water-based paint and preparation method thereof

    CN121950122A